Distribution and bioaccumulation of butyltins in the edible gastropod Odontocymbiola magellanica - del Brio, Federico Eduardo (2016)
Butyltins (BTs) were found in sediments and body tissues of the edible gastropod Odontocymbiola magellanica, in which imposex has been recorded since 2000. BTs in sediments ranged from < MDL to 174.8 ng (Sn) g−1 for TBT, < MDL to 19.2 ng (Sn) g−1 for DBT, and < MDL to 71.8 ng (Sn) g−1 for MBT. In body tissues BTs varied from < MDL to 147.1, < MDL to 77.0 and < MDL to 345.3 ng (Sn) g−1 for TBT, DBT and MBT, respectively. BT concentrations were higher in gonads and digestive glands than in the albumen gland and foot (edible). The highest concentrations of BTs in both sediments and gastropods were found in the harbour area, decreasing with distance to the harbour and areas with less maritime traffic. The Biota-Sediment Accumulation Factor (BSAF) in the different organs was between 0.02–0.42, 0.09–0.35 and 0.08–5.25 for TBT, DBT and MBT, respectively. There were positive correlations between concentrations of BTs in sediments and gastropod body tissues, suggesting that xenobiotic accumulation in O. magellanica occurs mainly through contaminated sediments, rather than water or the food chain. Considering current sediment quality guidelines, our results indicate that acute toxic effects would be expected from TBT exposure, which represents a serious environmental threat for the benthic community. Although the levels of BTs found in the foot of this edible gastropod did not exceed the recommended Tolerable Daily Intake in polluted areas, they should be monitored to ensure the safety of seafood consumers. The alternative antifouling biocides Irgarol and Diuron were not detected in sediments.